Long-lasting activity of trabectedin in refractory uterine leiomyosarcoma: a case report. Issue 1 (December 2015) - Bongiovanni, Alberto; Riva, Nada; Ricci, Marianna; Mercatali, Laura; Liverani, Chiara; La Manna, Federico; De Vita, Alessandro; Cavaliere, Davide; Pieri, Federica; Oboldi, Devil; Verdecchia, Giorgio; Amadori, Dino; et al.
Abstract Background Leiomyosarcoma (LMS) is an aggressive soft tissue sarcoma derived from smooth muscle cells typically of uterine, gastrointestinal or soft tissue origin. The prognosis for this tumor is poor, with survival rates among the lowest of all soft tissue sarcomas. Surgery is the best approach for localized disease. The principal role of chemotherapy is prevalently in the treatment of metastatic disease. Trabectedin, a promising new DNA-damaging agent with a mechanism of action that differs from that of traditional alkylating agents, has been approved in Europe for the treatment of patients with advanced soft tissue sarcoma after failure of anthracyclines and ifosfamide, Case presentation We report the case of a 53-year-old woman with metastatic well differentiated uterine leiomyosarcoma refractory to multiple treatments who underwent 22 cycles of trabectedin over 30 months, obtaining a partial response according to RECIST (Response Evaluation Criteria in Solid Tumors) criteria, with good tolerability, and maintaining the response for 10 months after trebectedin withdrawal. Conclusion This very prolonged response, which persisted after drug discontinuation, suggests that trabectedin exerts an oncostatic effect rather than the cytotoxic one produced by other chemotherapeutic agents. Our experience also raises the question of the best way to evaluate trabectedin efficacy.